PERILAKU BERBAGI PENGETAHUAN AKUNTANSI PADA DOSEN AKUNTANSI KOTA BENGKULU: PENDEKATAN THEORY OF PLANNED BEHAVIOR (TPB) - Madani Hatta; Baihaqi Baihaqi; Resti Ramahdaniati (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2017)
This study aims to determine the accounting knowledge sharing behavior at accounting lecturer in Bengkulu city, using the model theory of planned behavior influenced by three factor is attitude toward behavior, subjective norm, and perceived behavior control. Attitude toward behavior is influenced by factor self efficacy, social network, and extrinsic reward. While subjective norm is influenced by organization support. The population in this study were all accounting lecturer who worked in public and private universities in the city of Bengkulu using purposive sampling technique, so that the total sample of 62 people and data that can be used in this study were 43 respondents. Analysis technique using the assistance program smartPLS version 3 2.3. The results showed that self efficacy has positive affect on attitude toward behavior, social network has positive affect on attitude toward behavior, extrinsic reward has positive affect on attitude toward behavior, organizational support has positive affect on subjective norm, attitude toward behavior has positive affect on the accounting knowledege sharing behavior, subjective norm has positive affect on the accounting knowledege sharing behavior, and perceived behavior control has positive affect on the accounting knowledege sharing behavior.